IMPROVING BEGINNER STUDENT’S CHINESE LISTENING SKILLS THROUGH THE FLIPPED CLASSROOM METHOD: A ONE-GROUP PRETEST-POSTTEST STUDY AT UNIVERSITAS NEGERI SEMARANG - Anggraeni; Almira Agwinanda (Journal of Language and Literature, 2026)
This study investigates the use of the flipped classroom method to improve first-year students’ Chinese listening skills and examines their satisfaction with its implementation in the “Chuji Hanyu Tingli Xia” course. A one-group pretest-posttest quasi-experimental design was employed with 32 Mandarin Language Education students at Universitas Negeri Semarang, Indonesia. The intervention lasted six weeks and included pre-class listening materials, classroom discussion, peer correction, and teacher-guided practice. Data were collected using the HSK Level 3 listening test and a student satisfaction questionnaire. The results showed that students’ mean listening score increased from 67.19 to 78.59. A paired-samples t-test indicated a significant difference, t(31) = −4.790, p < .001, with a large effect size (Cohen’s dz = 0.85). The questionnaire results also indicated generally positive student satisfaction. However, the findings should be interpreted cautiously because no control group was used.